Analisis Kecelakaan Lalu Lintas di Jalan Yos Sudarso Kota Balikpapan - Rapsanjani Rapsanjani; Maslina Maslina; Wahidin Alauddin (Universitas Batanghari Jambi, 2026)
Road transportation plays a crucial role in supporting human mobility and the distribution of goods; however, traffic accidents remain a serious issue, particularly in urban areas with high activity levels. Yos Sudarso Road in Balikpapan City is a strategic corridor connecting major industrial zones with other key areas, resulting in complex traffic conditions and elevated accident risks. This situation highlights the need for a systematic analysis of traffic accidents along this roadway. The purpose of this study is to examine accident patterns, determine accident-prone conditions, and identify the main factors contributing to traffic accidents on Yos Sudarso Road. The research employs a quantitative approach using secondary data consisting of traffic accident records, road geometric data, location maps, and average daily traffic volumes from 2019 to 2023. Data analysis is conducted using the Accident Equivalent Number (AEN) method to assess accident severity and identify high-risk periods. The results indicate that traffic accidents fluctuate annually, with the highest AEN value recorded in 2022, reflecting a significant increase in accident severity during that year. Further analysis reveals that traffic accidents are predominantly influenced by unsafe rider behavior, inadequate road conditions due to surface damage, and environmental factors such as insufficient street lighting. In conclusion, Yos Sudarso Road can be classified as an accident-prone roadway. Therefore, integrated efforts are required, including infrastructure improvement, enhancement of road user awareness, and consistent law enforcement, to effectively reduce accident risks and improve overall traffic safety on this corridor.